ORNAMENT AS A MEANS OF ARCHITECTURAL AND ARTISTIC EXPRESSION (Neo Scientific Peer Reviewed Journal, 2026)
The article examines the traditional art of ornamentation, used as a means of architectural and artistic expression, which is used in modern construction. The article examines the traditional art of ornamentation, used as a means of architectural and artistic expression, which is used in modern construction.